ABSORPTION SPECTRA AND NATURE OF ELECTRONIC TRANSITIONS OF BISCYANINE DYES BASED ON QUINOLON-CONTAINING QUATERNARY SALT OF 4-METHYLPYRIDINIUM - Ягодинець, Петро; Скрипська, Ольга; Готинчан, Андрій; Барус, Маріанна; Горинюк, Ольга (SWorldJournal, 2024)
Biscyanine dyes were synthesized by the interaction of quinolone-containing quaternary salts of 4-methylpyridinium with p-diethylaminobenzaldehyde and 1,3,3-trimethyl-2-formylmethyleneindoline. Two absorption bands due to the interaction of chromophores w